SOCIAL BACKGROUND AND NARRATIVE IMAGES OF "KOBUSNOMA" - Bakhtiyorovna, Zaripova Dilfuza (International Journal of Psychosocial Rehabilitation, 2020)
There is no definitive information about the genre storytelling of the Eastern literature. They can only be found in the stories. The story is a confirmation of an incident that is in harmony with the content of the story to attract the reader. Caykovus also skillfully uses the genre of storytelling in "Kabusnama". The plot of the story in the "Kabusnama" is not entirely the same, but it sometimes reveals a meaningful intimacy and sometimes an ideological unity. The stories can be seen as a marvel of wondrous folklore, with unparalleled reverence, deep love and incomparable sincerity for the great folklore.